Impact of the low-carbon city pilot policy on green total factor productivity: a quasi-natural experimental design using an epsilon-based measure - Wu, Maoguo; Liu, Yihao; Huang, Linsong; Wang, Yuwei (Frontiers in Environmental Science, 2025)
Utilizing a panel dataset of 273 prefecture-level cities in China from 2000 to 2019, this study evaluates the impact of the low-carbon city pilot (LCCP) policy on green total factor productivity (GTFP). This study calculates GTFP via a hybrid function model of the epsilon-based measure. Using a staggered difference-in-differences framework, we found that the LCCP policy improves GTFP. Through its implementation, the LCCP policy exerts an increasingly positive impact. We identify promoting industrial structure optimization and technological innovation as two plausible underlying mechanisms. Heterogeneity analysis finds that the impact is more pronounced in central and western China, as well as in low-level administrative and low-marketization cities. This study provides empirical evidence for the optimization of the LCCP policy and the transformation of the low-carbon economy, and provides a basis for policy-making.